Enhanced Activation of mTOR Signaling Pathway Was Found in the Hypertrophic and Nodular Lesions of Port Wine Stains - Xu MN; Wang Q; Wang M; Xu Y; Yuan SM (Dove Medical Press, 2022)
Meng-Nan Xu,1,* Qian Wang,1,* Min Wang,1 Yuan Xu,1 Si-Ming Yuan1,2 1Department of Plastic Surgery, Jinling Hospital, Medical School of Nanjing University, Nanjing, Jiangsu, 210002, People's Republic of China; 2Department of Plastic Surgery, Jinling Hospital, Nanjing School of Clinical Medicine, Southern Medical University, Nanjing, Jiangsu, 210002, People's Republic of China*These authors contributed equally to this workCorrespondence: Si-Ming Yuan, Department of Plastic Surgery, Jinling Hospital, Medical School of Nanjing University, Nanjing, Jiangsu, 210002, People's Republic of China, Email yuansm@163.comBackground: Port wine stain (PWS) is a congenital skin lesion involving capillary malformations. Most PWS lesions will gradually become hypertrophic and appear nodular in contour. Current research shows that rapamycin, an mTOR inhibitor, is probably a promising adjunctive therapy for PWS, which suggests that the mTOR signaling pathway may play an important role in its pathological process.Methods: From January 2013 to January 2019, 13 samples were obtained during the surgical excision. Each sample was divided into 3 parts according to the type of lesion, namely, the flat, hypertrophic and nodular lesions. Pathologic structures of each type were observed under the microscope after HE staining. The expression of mTORC1, p70S6, p-p70S6, eIF4EBP1 and p-eIF4EBP1 was examined by immunohistochemical staining and western blotting. The location of the expression of mTORC1, p-p70S6 and p-elF4EBP1 was further detected by immunofluorescence staining.Results: Large amounts of dilated and malformed vessels were observed in all types of PWS lesions. Abundant hyperplastic hair follicles/glands were shown in the hypertrophic or nodular lesions. Phosphorylation level of p70S6 and elF4EBP1 in PWS was significantly higher than those in normal skin and increased accordingly in the progression of PWS. Activated molecules in mTOR signaling pathway were mostly located in the endothelium of malformed vessels. They were also located in the hyperplastic hair follicles/glands of hypertrophic and nodular lesions.Conclusion: The mTOR signaling pathway was increasingly activated during the progression of PWS. Enhanced activation of mTOR signaling pathway may contribute to the hypertrophy and nodularity of PWS. The results provide preliminary evidence for treating PWS and related syndromes by inhibiting mTOR signaling pathway.Keywords: port wine stain, mTOR signaling pathway